Myopic decisions under negative emotions correlate with altered time perception - Guan, Shuchen; Cheng, Lu; Fan, Ying; Li, Xianchun (Frontiers in Psychology, 2015)
Previous studies have obtained inconsistent findings about emotional influence on inter-temporal choice. In the present study, we first examined the effect of temporary emotional priming induced by affective pictures in a trial-to-trial paradigm on inter-temporal choice. The results showed that negative priming resulted in much higher percentages of trials during which smaller-but-sooner rewards (SS%) were chosen compared with positive and neutral priming. Next, we attempted to explore the possible mechanisms underlying such emotional effects. When participants performed a time reproduction task, mean reaction times in negative priming conditions were significantly shorter than those in the other two emotional contexts, which indicated that negative emotional priming led to overestimation of time. Moreover, such overestimation was negatively correlated with performance in the inter-temporal choice task. In contrast, temporary changes of emotional contexts did not alter performances in a Go/NoGo task (including commission errors and omission errors). In sum, our present findings suggested that myopic decisions under negative emotions were associated with altered time perception but not response inhibition.